Expression 13: "y" equals negative "x" left brace, 0 less than or equal to "x" less than or equal to 11 , right bracey=−x0≤x≤11
13
Expression 14: "y" equals 0 left brace, 0 less than or equal to "x" less than or equal to 8 , right bracey=00≤x≤8
14
Expression 15: "x" equals 8 left brace, 0 less than or equal to "y" less than or equal to 8 , right bracex=80≤y≤8
15
Expression 16: "y" equals 1 "x" left brace, 0 less than or equal to "x" less than or equal to 8 , right bracey=1x0≤x≤8
16
Expression 17: "y" equals 2 left brace, negative 1 less than or equal to "x" less than or equal to 1 , right bracey=2−1≤x≤1
17
Expression 18: "y" equals negative 1 "x" plus 3 left brace, 1 less than or equal to "x" less than or equal to 2 , right bracey=−1x+31≤x≤2
18
Expression 19: "x" equals 2 left brace, negative 1 less than or equal to "y" less than or equal to 1 , right bracex=2−1≤y≤1
19
Expression 20: "y" equals 1 "x" minus 3 left brace, 1 less than or equal to "x" less than or equal to 2 , right bracey=1x−31≤x≤2
20
Expression 21: "y" equals negative 2 left brace, negative 1 less than or equal to "x" less than or equal to 1 , right bracey=−2−1≤x≤1
21
Expression 22: "y" equals negative 1 "x" minus 3 left brace, negative 2 less than or equal to "x" less than or equal to negative 1 , right bracey=−1x−3−2≤x≤−1
22
Expression 23: "x" equals negative 2 left brace, negative 1 less than or equal to "y" less than or equal to 1 , right bracex=−2−1≤y≤1
23
Expression 24: "y" equals 1 "x" plus 3 left brace, negative 2 less than or equal to "x" less than or equal to negative 1 , right bracey=1x+3−2≤x≤−1